A study on the level of stress and stress factors among trained teachers in selected Zone B secondary schools in Miri, Sarawak - Wong, King Kui (1999)
The purpose of this study is to investigate the level of job stress and the factors causing stress among teachers in zone B Secondary School in Miri, Sarawak. The study also attempts to determines if there are differences in the level of stress and main stressors based on the demographic characteristics investigated are gander, marital status, age group, academic qualification, number of periods per week and number of years of teaching experiences.